1238 Psychosocial risk for survivor drivers in work-related road traffic fatalities. (24th April 2018) - Drummond, A; Codd, M
Abstract : Introduction: Work-related road-traffic management is recognised as an important means of both occupational and public accident prevention. This area is of concern to road safety, public health, and occupational health and safety regulatory authorities. However, the psychological risk for workers who survive work-related fatal collisions is rarely considered. Methods: A retrospective descriptive study was conducted using data from all coroner road traffic fatality records in the Republic of Ireland, focusing on deaths that occurred in the calendar years 2008 to 2011 inclusive. Data were used to ascertain the prevalence and nature of work-related road traffic fatalities, and to identify work-related accident prevention opportunities. Results: It was ascertained that 23% (n=193) of all road-traffic fatalities (n=833) were work-related. In 15% of cases a worker died; however, in 85% of cases a 'bystander' died and the (worker) driver of the involved vehicle survived. Surviving drivers comprised mostly professional drivers: truck drivers (52%), public service vehicle drivers (20%) and van drivers (12%). In 27% of bystander deaths work contributed to the collision, but in the majority the worker driver's actions did not contribute to the collision. Depositions from survivors and witnesses attested to the trauma visited on workers who survived such collisions, however no evidence was found suggesting psychological support for driver survivors. Discussion: Many workers drive for a living and others drive occasionally as part of work. Work-related driving policies tend to focus on ensuring that worker drivers' vehicles and practices are safe. However, little account is taken of the psychosocial risk and the impact of the unsafe driving practices of other road users on survivor drivers, who are party to fatal collisions. These findings have implications for occupational risk assessment and tertiary prevention strategy planning, including post-traumatic counselling, reintegration into work and employee assistance programmes.